Complete Blood Count-Derived Indices as Prognostic Factors of 5-Year Outcomes in Patients With Confirmed Coronary Microvascular Spasm - Bil, Jacek; Pietraszek, Natalia; Gil, Robert J.; Gromadziński, Leszek; Onichimowski, Dariusz; Jalali, Rakesh; Kern, Adam (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary microcirculatory dysfunction is a meaningful factor in the development of ischemic heart disease. We investigated the relationship between coronary microvascular spasm and complete blood count indices. Methods: Between 2010 - 2013, we performed acetylcholine test (AChT) in subjects with suspicion of angina evoked by epicardial coronary spasm or coronary microvascular spasm according to COVADIS criteria. We administered acetylcholine in increasing doses of 25, 50, and 75 mcg into the right coronary artery and 25, 50, and 100 mcg into the left coronary artery. Patients were followed up for 60 months. Results: In total, 211 patients (60.5±7.8 years, 67.8% women) were included in the study. The AChT revealed angina due to epicardial coronary spasm in 99 patients (46.9%) and coronary microvascular spasm in 72 (34.1%). White blood cell (WBC), red blood cell distribution width (RDW), platelets (PLT), mean platelet volume (MPV), and platelet distribution width (PDW) values were signiﬁcantly higher in patients with coronary microvascular spasm than in patients from the other two groups, i.e. epicardial coronary spasm and negative AChT. PDW showed the highest sensitivity (65%) and specificity (72%) at the cutoff value of 15.32% (area under the curve, 0.723; 95% confidence interval [CI] 0.64–0.83; P < 0.001). Independent risk factors for coronary microvascular spasm diagnosis using AChT were as follows: female sex (OR, 1.199), PDW (OR, 2.891), and RDW (OR, 1.567). Conclusions: PDW and RDW are significantly associated with the diagnosis of coronary microvascular spasm in patients undergoing AChT as well as with poor prognosis in such patients at 5 years.